Developing Lexical Competence in Educational Institutions - Dilshoda Kakhramonovna Maksudova; Aliyeva Muxlisa Baxodir Qizi (Journal of Learning on History and Social Sciences, 2024)
This article is importance of lexical skills in the context of interdisciplinary relations as an integral part of the lexical competence of a foreign language is emphasized, their specificity and conditions of formation are described, based on the advantage of constructing a lexical competence of a foreign language on an interdisciplinary basis. This involves taking into account the linguistic characteristics of the students as well as the educational and cognitive activities.